Preparation, Characterization and Application of Nano ZnO - Blended Polymeric Membrane. (2018) - Rajeswari, A.; Pius, Anitha
Abstract: Effluents from dyeing and finishing processes of textile industry contain strong colour and possible heavy metals. Conventional treatments are applied to treat dyes but the secondary pollution problem not addressed. Consequently, the heterogeneous photocatalytic oxidation process is of special interest. In this work a cellulose acetate-polyethylene glycol-polyurethane membrane impregnated with nano ZnO as a photocatalyst was prepared. The prepared membranes characterized by IR, SEM with EDAX and pure water flux (PWF). The photocatalytic degradation of dyes using prepared membrane was investigated towards the removal of Reactive red and Reactive orange. The kinetic model of Langmuir-Hinshelwood well describes the photodegradation capacity.